2019
DOI: 10.15282/jmes.13.2.2019.05.0402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orifice geometry and orifice to test section spacing on distribution of wall static pressure on a convex surface

Abstract: The experimental investigation is carried out to study the distribution of wall static pressure (Cp & Cpo) on the convex smooth surface by air jet impingement. A great deal of attention was paid to analyze the effects of orifice geometry for various flow and geometric conditions, a comparison of the wall static pressure coefficient is done for different orifice. The experimental results show that the wall static pressure on a convex test section is higher for rectangular orifice compared to other orifice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…The graph of CP vs θ shows the independent characteristic of jet Re on the distribution of non-dimensional CP and CPO value for all Z/dj = 1 to 5 in both confined and unconfined flow condition, as all the curves take same profile for all jet Re (50000-10000) with some minor deflection in CP magnitude. Similar independency of jet Reynolds nd CPo was observed and highlighted in most studies [23][24][25]. It is also observed that the CP and CPo are dependent on flow restriction and non-dimensional jet exit distance (Z/dj) and lateral distance (X/dj) which are discussed in other sections.…”
Section: Influence Of Jet Reynolds Number On Wall Static Pressuresupporting
confidence: 81%
See 2 more Smart Citations
“…The graph of CP vs θ shows the independent characteristic of jet Re on the distribution of non-dimensional CP and CPO value for all Z/dj = 1 to 5 in both confined and unconfined flow condition, as all the curves take same profile for all jet Re (50000-10000) with some minor deflection in CP magnitude. Similar independency of jet Reynolds nd CPo was observed and highlighted in most studies [23][24][25]. It is also observed that the CP and CPo are dependent on flow restriction and non-dimensional jet exit distance (Z/dj) and lateral distance (X/dj) which are discussed in other sections.…”
Section: Influence Of Jet Reynolds Number On Wall Static Pressuresupporting
confidence: 81%
“…This result indicates that high pumping power is required in the confined flow. Similar contributions are observed for circular, square, rectangular and triangular orifice in early studies [23]. journal.ump.edu.my/ijame ◄…”
Section: Comparison Of Wall Static Pressure For Confined and Unconfinsupporting
confidence: 79%
See 1 more Smart Citation
“…Like the parameters of the flow, the geometry of the jet orifice or the nozzle plays a critical role in the production of self-sustaining tones [10][11][12][13][14][15][16][17]. Sondhauss et al [18] showed that the Strouhal number relative to the frequency transmitted depends both on the distance between the jet outlet and the slotted plate, and on the speed of the jet, while remaining within the upper and lower limits of the velocity range that corresponds to the appearance of self-sustaining sounds.…”
Section: Introductionmentioning
confidence: 99%